Queer community : identities, intimacies, and ideology - Carnes, Neal (London : Routledge, Taylor & Francis Group, 2019)
The context for this work is defined by a second wave of social and political activity contextualized by queer. For example, three, self-identified black, queer women started the Black Lives Matter movement. For a new generation, the first-wave reclamation of queer speaks to their position in a world that continues to marginalize and oppress, particularly sexually and gender fluid and non-normative people. Using empirical work carried out by the author, Queer Community describes queer-identified people, their intimate relationships, and how they are evolving as a unique community along politically-charged, ideological lines. Following an exploration of the history and context of 'queer' - including activism and the evolution of queer theory - this book examines how queer-identified people define the identity, with reference to 'queer' as a sexual moniker, gender moniker, and political ideology. Queer Community will appeal to scholars and students interested in sociology, queer theory, sexuality studies, gender studies, cultural studies, and contemporary social movements.
Queer as an identity"Don't yuck my yum": policing queer; Queer aesthetics and body image; The personal is political and the political is personal; Code for conduct; Performing queer; Fighting the good queer fight; "Southern Fried, Queer Pride": queer in Atlanta; 4 "We're here, we're queer, and we ain't going nowhere": The evolution of queer community; Implications for queer theory and theoreticians; Conclusion; References; Glossary; Appendix: Methods; Index
OCLC-licensed vendor bibliographic record.
Keywords: Gender identity; Queer theory; Queer theory -- Social aspects; Sexual minorities -- Political activity; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General